Computer networks and internets : with internet applications. - Comer, Douglas Earl, 1949- (New Jersey : Pearson Education, 2004)
COURSE = For one-semester, undergraduate/graduate introductory computer networking courses in Computer Science, Electrical Engineering, CIS, MIS, and Business Departments. Written by a best-selling author and leading computer networking authority, this book builds a comprehensive picture of the technologies behind Internet applications. It answers the basic question "how do computer networks and Internets operate?" in the broadest sense and includes an early optional introduction to network programming and applications. The book provides a comprehensive, self-contained tour through all of networking from the lowest levels of data transmission and wiring to the highest levels of application software, explaining how underlying technologies provide services and how Internet applications use those services. At each level, it shows how the facilities and services provided by lower levels are used and extended in the next level. Emphasis on Internet technologies and applications provides readers with substantial sections on Internetworking and Network Applications. For individuals with little or no background in the subject.
Keywords: Computernetwerken; Internet